2015
DOI: 10.1002/app.42928
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of anion‐exchange resins with Mg/Al double‐metal hydroxides

Abstract: Anion-exchange resins (AERs) were regenerated with Mg/Al double-metal hydroxides as the regenerant. Electrical conductivity breakthrough curves were adopted to estimate the relatively rapid regenerative effect of the AERs. The results show that the optimal regenerative effect of AER was obtained when the Mg/Al molar ratio was 3 and the dosages of Mg and Al hydroxides were 0.045 and 0.015 mol, respectively. The highest effluent water yield was obtained at an AER/cation-exchange resin volume ratio of 2:1. Charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Up to now, the role of CuS loaded on chalcogenides in improving the photocatalytic efficiency is controversial. Wang et al 33 suggested that CuS as a cocatalyst served as trapping sites for photogenerated electrons, while Shen and coworkers 23 postulated that CuS as a cocatalyst trapped holes. As we know, a photocatalytic reaction occurs at the interface between catalyst surface and solution.…”
Section: Photogenerated Charge Transfer Propertiesmentioning
confidence: 99%
“…Up to now, the role of CuS loaded on chalcogenides in improving the photocatalytic efficiency is controversial. Wang et al 33 suggested that CuS as a cocatalyst served as trapping sites for photogenerated electrons, while Shen and coworkers 23 postulated that CuS as a cocatalyst trapped holes. As we know, a photocatalytic reaction occurs at the interface between catalyst surface and solution.…”
Section: Photogenerated Charge Transfer Propertiesmentioning
confidence: 99%